The Non-Parameter Evaluation of the Quality of Education in European Countries Based on Panel Data - Krstić Srejović, Ana; Mimović, Predrag; Jakšić, Milena (Journal of Public Governance, 2024)
Objective: The aim of this paper is to evaluate the performance of sustainable development in the education sector through a relative comparison of thirty-five European countries in the period of 2013–2021. Sustainable Development Goal number 4, namely the quality of education, was taken as a benchmark for evaluation.Research Design & Methods: The performance of the countries was evaluated using the combined Slack Based Measure DEA Window model, which has a higher discriminating power than the standard DEA model and a dynamic dimension of observation. Finally, the robustness and sensitivity of the results was tested using bootstrapping methods.Findings: The results showed that the performance of the quality of education, measured in terms of the DEA concept of efficiency, in the period 2013–2021, was at a relatively low but stable level overall. It was shown that, above all, the observed countries that are not members of the EU achieved a far worse level of the quality of education in the observed period, including the United Kingdom.Contribution / Value Added: The obtained results are important in terms of benchmarking public policies related to sustainable development, especially in terms of contributing to discussions regarding the evaluation of countries’ performance, especially in the field of education, as one of the key goals of sustainable development. Also, the results refer to the sources of the inefficiency of educational policies, primarily in countries that are not members of the European Union, but also in some of the member countries.Article classification: research articleJEL classification: C61, H52, I25